In vitro mass propagation and conservation of a rare medicinal plant, Zhumeria Majdae Rech.f & Wendelbo (Lamiaceae). (January 2019) - Fallah, Maryam; Farzaneh, Mohsen; Yousefzadi, Morteza; Ghorbanpour, Mansour; Mirjalili, Mohammad Hossein
Abstract: The monotypic Zhumeria majdae (Lamiaceae), an endangered medicinal and aromatic plant in the south part of Iran, has a low propagation rate in natural condition and therefore an efficient method for the in vitro -propagation is required. In the present study, the effects of source and position of the explants as well as various concentrations of 6-benzylaminopurine and kinetin on inhibition of hyperhydricity and in vitro mass propagation of the plant were investigated. The best shoot formation (1.9 ± 0.07) was obtained with a Murashige and Skoog medium fortified with 17.7 µM 6-benzylaminopurine. Regenerated shoots, elongated on the MS medium containing 2.2 μM 6-benzylaminopurine, were rooted on the different tested media, with the most abundant (68.6 ± 4.1%) and strongest roots obtained on half-strength medium without plant growth regulators. Hydro-distilled essential oils of in vitro regenerated plant were analyzed by gas chromatography–mass spectrometry and compared with the essential oil of wild plant. Thirty and twenty compounds representing 98.2% and 98.7% of the total oils were identified in the oils of wild plant and in vitro regenerated plant, respectively. The major essential oil components were linalool (31.7% and 41.7%), camphor (28.0% and 32.4%), limonene (4.6% and 8.3%), camphene (4.1% and 3.5%) and E- caryophyllene (1.0% and 2.7%) in the studied (wild plant and in vitro regenerated plant) essential oils. The in vitro regeneration system could be utilized for both conservation, large-scale multiplication and production of rich linalool essential oils of Z. majdae .